Determinantes da adoção de smartphones e ferramentas de compartilhamento de mensagem por produtores rurais - Mendes, Juliana de Jesus (Universidade Federal de São Carlos, 2023)
This study aimed to identify the determinants of farmers’ participation in agricultural information-sharing digital groups and their impacts on farm performance. The work was organized in the format of two scientific articles. The first article presents a systematic literature review on the determinants of the adoption of digital innovations by farmers from different countries. Articles in the period of 2010 to 2022 were reviewed in three databases: Scopus, Periódicos Capes and Science Direct. From an initial base of 131 articles, 21 were selected for the purposes of this review. The review showed a diffuse geographic distribution of the studies, with emphasis in Brazil and Germany. The analysis of the results of the reviewed articles indicated a total of 21 determining factors. Factors related to the business and human capital/personal characteristics of the farmers were the most relevant to determine the adoption of technologies. The scale of production proved to be a determining factor of adoption in approximately 85% of the analyzed articles, followed by two personal aspects: education and age (a generally negative effect). The second article presents econometric analyzes of the determinants of farmers’ participation in agricultural information-sharing digital groups, as well as their impacts on farms performance. Primary data of the 2015/2016 crop year collected from 175 cattle farmers were analyzed using descriptive statistics and econometric models. Farmers who had smartphones and participated in social groups/applications, especially those created to exchange agricultural information, were considered adopters of the technology. A Poisson hurdle model showed that farmers’ decision to participate in agricultural information-sharing digital groups is determined by schooling, age (negative effect) and use of tools for planning production. The intensity of participation is affected by risk propensity, interaction with specialist advisors, use of tools for planning production and participation in cooperatives. The authors also found empirical evidence that farmers’ participation in agricultural information-sharing digital groups positively affects farm income per hectare. The results of this dissertation are important to accelerate the diffusion of digital technologies in agriculture. The diffusion of these technologies is important to reduce heterogeneity and increase the economic well-being of producers.
Determinants of adoption of smartphones and message sharing tools by rural producers
Keywords: Tecnologias digitais; Adoção de inovações; Acesso à informação; Impacto; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA